Następcza niemożność świadczenia wynajmującego z terminowej umowy najmu - Adamus, Rafał (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
The subject of the analysis in this study is the issue of a term lease agreement, the termination of which (exercising the formative right) requires certain conditions to be met. However, in the case of a timely lease agreement, there may be a situation in which it is not possible for the landlord to fulfill the service in accordance with its content and in a way that corresponds to its socio-economic purpose and the principles of social coexistence. Such an impossibility may result from circumstances independent of the parties of the legal relationship. The consequence of the subsequent impossibility of providing service – no fault of parties – is the expiry of the term lease agreement. The expiry of the lease has effect under the law itself.
Keywords: rental agreement; inability to provide contractual benefit; term contract; contract termination